2020
DOI: 10.1002/cnma.202000531
|View full text |Cite
|
Sign up to set email alerts
|

Camellia Pollen‐Derived Carbon with Controllable N Content for High‐Performance Supercapacitors by Ammonium Chloride Activation and Dual N‐Doping

Abstract: Biomass‐derived carbon materials are an amazing electrode material for supercapacitor, owing to their abundant, porous structure and composition. Herein, a controllable N content carbon material with hierarchical porous structure was fabricated via an integrated carbonization, activation and nitrogen‐doping process. N‐rich camellia pollen is used as carbon precursor, while NH4Cl is employed as both activation agent and dopant. The optimal N‐doped carbon with higher N content (3.82 at%), suitable pore size dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Similar to BCs, the structure of all ACs is also amorphous, in agreement with that reported in previous studies. 42 44 However, ACs possess stronger diffraction peaks than BCs. Furthermore, the fraction peaks of ACs shift to a greater 2θ angle direction, indicative of enhanced graphitization degree due to activation at a high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to BCs, the structure of all ACs is also amorphous, in agreement with that reported in previous studies. 42 44 However, ACs possess stronger diffraction peaks than BCs. Furthermore, the fraction peaks of ACs shift to a greater 2θ angle direction, indicative of enhanced graphitization degree due to activation at a high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The R CT values of DAC-600, DAC-700, and DAC-800 are 0.59, 0.10, and 0.23 Ω, respectively. The R CT of DAC-700 is obviously lower than that of DAC-600 and DAC-800, which is more beneficial to the energy storage of N, P-containing groups on the surface of DAC-700 electrode through chemical reaction . In the low frequency region of the Nyquist plots, the curves of DAC-700 and DAC-800 were evidently steeper than that of DAC-600.…”
Section: Resultsmentioning
confidence: 92%
“…The R CT of DAC-700 is obviously lower than that of DAC-600 and DAC-800, which is more beneficial to the energy storage of N, P-containing groups on the surface of DAC-700 electrode through chemical reaction. 33 In the low frequency region of the Nyquist plots, the curves of DAC-700 and DAC-800 were evidently steeper than that of DAC-600. This phenomenon indicated that the hierarchical pore structure of DAC-700 and DAC-800 is conducive to the migration of ions in the electrode, which lead to a relatively lower Warburg diffusion resistance ( Z w ).…”
Section: Resultsmentioning
confidence: 95%
“…Camellia japonica (camellia) is an ornamental flower that is widely distributed in East Asia. Considering that the camellia is rich in anionic heteroatoms, it can be a valuable biomass feedstock for the synthesis of biochar 35,36 …”
Section: Introductionmentioning
confidence: 99%
“…Considering that the camellia is rich in anionic heteroatoms, it can be a valuable biomass feedstock for the synthesis of biochar. 35,36 In this study, sulfur self-doped activated camellia (SA-Came) nanospheres were prepared using a solvothermal-pyrolysis method with camellia flowers as raw materials. During the process, sulfur atoms were naturally doped into the carbon nanospheres without additional doping precursors.…”
Section: Introductionmentioning
confidence: 99%